The Impact of IoT Marketing Automation and Data Quality on Increasing Sales of Fashion MSMEs in West Java - Frans Sudirjo; Muhamad Ammar Muhtadi; Rival Pahrijal (Westscience Press, 2025)
The rapid development of digital technologies has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt more advanced marketing strategies to remain competitive. This study investigates the impact of IoT marketing automation and data quality on the sales growth of fashion MSMEs in West Java. A quantitative research approach was employed using primary data collected from 250 fashion MSME owners and managers through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using SPSS version 25, applying descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that IoT marketing automation has a positive and significant effect on sales growth, demonstrating that automated and data-driven marketing activities enhance marketing efficiency and customer engagement. Data quality also shows a positive and significant effect on sales growth, highlighting the importance of accurate, complete, timely, and relevant data in supporting effective marketing and sales decisions. Furthermore, the simultaneous analysis reveals that IoT marketing automation and data quality jointly contribute significantly to explaining sales growth among fashion MSMEs. These findings suggest that successful digital transformation in MSMEs requires not only the adoption of IoT-based marketing technologies but also strong data management practices. The study provides practical insights for MSME practitioners and policymakers in designing strategies to strengthen digital capabilities and improve business performance in the fashion sector.